Tayma, Saudi-Arabien: Reflectance Transformation Imaging: Innovative Dokumentationstechnologie in der Archäologie - Hausleiter, Arnulf (e-Forschungsberichte des DAI, 2023)
A series of archaeological artefacts from the excavations at Tayma have been recorded by Reflectance Transformation Imaging (RTI), “an innovative computational photographic method capturing shape and colour of the surface of the archaeological artefacts” (www.culturalheritageimaging. org). Enabling the interactive re-lighting of the object from any direction, it is an extremely useful tool for archaeologists and epigraphers. In addition to a total of 158 objects, among them the majority of the inscriptions, human bones and pottery have been recorded in collaboration with DAI’s ITDepartment.